Teachers Views and Perceptions towards the Lesson Study Processes - Wahyudi Wahyudi; Warabhorn Preechaporn (Southeast Asian Mathematics Education Journal, 2011)
The key to professional development is inquiry. For teachers, it means that they become researchers, inquiring into their own practices for purposes of professional renewal. Lesson Study has been widely accepted as an embedded teacher professional development process. This paper reports on primary school mathematics teachers’ view and perceptions toward Lesson Study processes as a mean for their continuous professional development. After their exposure to Lesson Study processes from a four week course at RECSAM, the researchers sought their views and experiences with conducting Lesson Study. The respondents were primary school mathematics teachers and teacher’ educators who participated in courses conducted at SEAMEO RECSAM, Penang, Malaysia. The data were drawn through interview and from their project works, journals, reports, and questionnaires. This study noted that most of the teachers held positive but reluctant views on Lesson Study as a path for continuous professional development. They agreed that Lesson Study can be used as effective tool for their professional development under specific circumstance. Possible factors that support and hinder teachers to be engaged in Lesson Study were noted such as flexible time table, teacher’s experiences and supportiveschool policy.